Use of traditional knowledge in weather prediction and averting climate risks: A case study in livestock‐based smallholder farming systems in Sri Lanka. Issue 6 (21st May 2022) - Siriwardana, Amila Nuwan; Samarakone, Thusith Semini; Silva, Gamameda Liyanage Lalanie Pradeepa; Dematawewa, Chandrarathne Mahinda Bandara; Punyawardena, Batugedara Vidanalage Ranjith; Marambe, Buddhi; Nidumolu, Uday; Howden, Mark
Abstract: Background: Integration of traditional knowledge (TK) to decision making in agriculture is a continued practice of the smallholder farmers in the tropics. There is a knowledge gap in the use of TK in weather or climate prediction by farmers to minimize climate risks. Hence, a field survey was conducted using a pre‐tested questionnaire coupled with key informant discussions. The study focused on the farmers practicing livestock‐based farming systems in Thabbowa village of the north‐western province of Sri Lanka. Results: About 94% of farmers had access to national level weather forecasting (WF); however, 54% were not confident enough of the accuracy of the WF. Only elderly farmers had confidence in predicting the weather using TK. While using the outcome of the production, those elderly have passed the outcome of the TK‐based weather predictions (WP) to the rest of the farmers where 46% of the study sample used such information at some level of decision making in agriculture. However, it was evident that the farmers used TK‐based WP combined with the national level WF for deciding on agricultural operations. Plant phenology, animal behavior and astronomical evidence were the commonly used biotic and abiotic factors in TK for WP. The behavior of birds was the prominent TK‐based animal indicator for short to medium range and seasonal WP. Conclusion: The smallholder farmers need to be strengthened to use national WF with the correct application of TK‐based WP to fulfill the gaps in deciding climate‐adaptation strategies in mixed‐farming systems.